Islamic and conventional bank market value: Manager behavior and investor sentiment - Mouna Abdelhedi-Zouch; Achraf Ghorbel (Cogent Business & Management, 2016)
This paper studies the effect of bank manager behavior and investor behavior on market value of Islamic and conventional banks in the Middle East and North Africa region. Firstly, our analysis denoted the positive effect of discretionary behavior of manager on both types of banks on share prices since discretionary behavior transmits to investor a positive signal of future earnings' prospects. Also, we find that the conventional bank stock prices response is very high to negative signal compared with positive signal. This result is explained by prospect theory and loss aversion bias which specified that individuals are more sensitive to losses than gains of same magnitude. In particular, we discover that the negative effect of non-discretionary behavior is much lower on Islamic bank value since investors give more confidence to Islamic bank because they are motivated by the idea that Islamic banks are safer than conventional banks. Secondly, the results show that investor sentiment affects significantly both bank market prices. Thus, both Islamic and conventional banks' market value depends similarly on manager and investor behavior. The implication of this paper is that Islamic bank concentrations reveal a positive effect on their price values because of the recently increased investments in Islamic banks.
Keywords: 650